Sequential Sterilization of Banana (Musa Spp.) Sucker Tip Reducing Microbial Contamination With Highest Establishment Percentage (Bangladesh Journal of Botany, 2021)
Sterilization procedure was standardized for grand naine cultivar of banana using various sterilants in combinations and alone. The observations were recorded regularly with respect to presence of fungal, bacteria as well as percentages of culture establishment. Results indicated that a treatment combination No. 3 [Lactic acid (0.15 %) + Tween-20 (0.1 %) + 0.8 % Commercial bleach (30 Min.) followed by Sodium chlorite (0.3 %) (20 min)] gave the highest percentage of aseptic culture establishment in vitro condition. The present study also showed that, single step aseptic inoculation was unable to control endophytic contaminants while sequential treatments were good enough to reduce microbial load as well as increase culture survival.Bangladesh J. Bot. 50(4): 1151-1158, 2021 (December)